The Positive Influence of Traditional Classical Literature Reading Promotion Activities on Mental Heath - Jingjing Li (Forest Chemicals Review)
In the educational environment of the lack of traditional Chinese classics, fragmented reading causes anxiety and negative emotion, it is particularly important to effectively cultivate learners healthy psychological personality through reading promotion activities, and form a classic reading context based on cultivating healthy psychological personality, and construct a classic reading leading mechanism. Through a large number of sample network survey and field research, the analysis report is formed by studying the reading tendency, reading habit, reading level and reading time of college learners. Generally speaking, users’ satisfaction with obtaining information resources of classical Chinese literature is positively related to the comprehensiveness of library information resources and library services. Therefore, it is necessary to analyze the current situation of the lack of psychological and cultural intensive reading of contemporary learners, and in view of the lack of learners’ understanding of traditional classical culture, carry out accurate reading guidance services based on traditional Chinese culture and traditional Chinese classics. This paper expounds the importance of mental health through the examples of healthy psychological character. Through the promotion of Chinese classic reading activities, we can effectively improve learners’ mental health and enable learners to establish a good view of life, values and world. Mental health plays a positive role in social development. This paper explores how to use reading promotion to cultivate learners’ healthy psychological personality, and through a questionnaire survey, discusses the effectiveness of the promotion of traditional classical literature reading. Reading Classic Literature can effectively relieve learners’ anxiety, solve their daily social problems and improve their study interests.